2008
DOI: 10.1002/chem.200800860
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Sapphyrin: Towards Selective Phosphate Binding

Abstract: The anion-templated syntheses and binding properties of novel macrocyclic oligopyrrole receptors in which pyrrole rings are linked through amide or imine bonds are described. The efficient synthesis was accomplished by anion-templated [1+1] Schiff-base condensation and acylation macrocyclization reactions. Free receptors and their host-guest complexes with hydrochloric acid, acetic acid, tetrabutylammonium chloride, and hydrogen sulfate were analyzed by single-crystal X-ray diffraction analysis. Stability cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In related studies, the bipyrrole-derived macrocycles 851-854 were synthesized by Katayev and co-workers. 867 Competitive 1 H NMR spectroscopic titrations were performed in the presence of acetate in DMSO / 0.5% water. These experiments revealed that receptor 852 displayed selectivity toward dihydrogenphosphate (TBA salt).…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…In related studies, the bipyrrole-derived macrocycles 851-854 were synthesized by Katayev and co-workers. 867 Competitive 1 H NMR spectroscopic titrations were performed in the presence of acetate in DMSO / 0.5% water. These experiments revealed that receptor 852 displayed selectivity toward dihydrogenphosphate (TBA salt).…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…61 Tripyrrolic macrocycles have been synthesized and tested in DMSO-0.5% water, and they show high affinity for bifluoride, while their larger tetrapyrrolic analogues do not. 62 Calixpyrroles, whose name derives from the structural similarity with calixarenes, are tetrapyrrolic macrocycles which were obtained for the first time in the end of 19th century, and were only recently rediscovered as anion, 63 and as ion-pair receptors. 64 The octamethylcalix [4]pyrrole 34 (Scheme 5) has received considerable attention and has been extensively studied from both experimental and theoretical point of view.…”
Section: Pyrrolic and Indolic Nhsmentioning
confidence: 99%
“…114 When the pyridine part of diamine 145 was replaced by 2,2′bipyrrole, the resulting diamine 156 is also regarded as a useful building block for macrocycles. Katayev et al 115,116 reported reactions of 156 with various dipyrrolic building blocks to produce [1 + 1] macrocycles 157−159 in good yields (Scheme 42). H 2 PO 4 − , as a TBA + cation, acted as an anion template in the preparation of 157, which increased the yield to 57% from the 15% yield without template.…”
Section: Schiff-base Oligopyrrolic Macrocyclesmentioning
confidence: 99%